Divers' infectious pathologies in severe climate - V. I. Pustovoit; A. S. Samoilov; R. V. Nikonov (National Electronic Information Consortium (NEICON), 2020)
Objective: to improve the methodology of timely functional body's reserves assessment, to reduce the probability of an infectious disease in divers during the training and competition period in the countries with severe climate. Materials and methods: We performed the mathematical and statistical analysis of the examination data and the frequency of infectious diseases in 2018-2019 in 47 male divers (mean age 30,5±3,56). Th e study involved volumetric compression oscillometry (VKO) and heart rate variability (HRV). Results: in the volumetric compression oscillometry and heart rate variability analysis, we determined the most signifi cant (p<0,05) signs (systolic and diastolic blood pressure, mean hemodynamic and lateral arterial pressure, energy consumption for the movement of one liter of blood, total and specifi c peripheral vascular resistance, root mean square deviation, square root of the sum of the diff erences in a series of cardio intervals, Max-Min diff erence, Max / Min ratio, mode 50 amplitude, mode 7,8 amplitude and stress index of regulatory systems). Th ese signs enable timely evaluation of the divers' functional state indicating a premorbid or critical health level. Th e study fi ndings allow prediction of probable health complications. Conclusions: regular health monitoring enables the timely diagnosis of the adaptive mechanism disorders associated with decreased antiviral and antimicrobial resistance of divers. Th e methodology for the body functional state evaluation is proposed which has high diagnostic value and is based on the VKO and HRV assessment. Th e methodology of the integrated assessment for extreme and critical conditions has a close correlation (p˂0,05; r˃0,70) with acute infectious diseases.